Partisipasi Penyusunan Anggaran, Pemanfaatan Aplikasi Sistem Keuangan dan Sistem Pengendalian Intern terhadap Kinerja Manajerial PT. Fumira - Dwi Anie Mayasari; Iin Indarti; Nurdhiana Nurdhiana (Jurnal Ilmiah Aset, 2023)
This research was to find out and analyze the effect of budgeting participation, utilization of financial system applications and internal control systems on managerial performance of PT. FUMIRA in 2021. This research is an associative quantitative research. The method used in this research was a survey either partially or simultaneously through a questionnaire. The sample of this research was the entire management leadership of PT. FUMIRA, totaling 59 people. The sampling technique used was saturated sampling, where all members of the population are used as research samples. The analytical tool used in this research was multiple linear regression analysis. Based on the results of data processing, it can be concluded that: Partially, budgeting participation, utilization of financial system applications and internal control systems have a significant positive effect on managerial performance. Simultaneously budgeting participation, utilization of financial system applications and internal control systems simultaneously have a significant effect on managerial performance by 60.2%.